Anaphothrips sineconus and Hyalopterothrips brunneus, two new species of Anaphothrips genus-group (Thysanoptera) from Iran - Alavi, Jalil; Yazdanian, Mohsen; Minaei, Kambiz (Zootaxa, 2018)
Anaphothrips sineconus sp. n. is described as unique within the genus for the absence from antennal segment III of a sense cone and reduction in some other character states. Hyalopterothrips brunneus sp. n. is similar to H. crocatus and H. hieroglyphicus in having forked sense cones on antennal segments III–IV. Both new species are collected on the plant family Amaranthaceae in the East of Iran.